Prolinamide plays a key role in promoting copper-catalyzed cycloaddition of azides and alkynes in aqueous media via unprecedented metallacycle intermediates. Issue 11 (22nd March 2021) - Chakraborti, Gargi; Jana, Rajkumar; Mandal, Tirtha; Datta, Ayan; Dash, Jyotirmayee
Abstract : Room temperature copper-catalyzed cycloaddition of azides and alkynes (CuAAC) proceeds in the presence of a prolinamide ligand in aqueous media via unique metallacycles. Abstract : We herein delineate cycloaddition of a wide range of azides with terminal alkynes using catalytic CuI and a prolinamide ligand in aqueous media under aerobic conditions. The catalytic system is used for a 'one-pot' synthesis of triazoles from aliphatic halides and alkynes. A detailed computational study predicts that prolinamide plays a unique role in facilitating the cycloaddition in water via the formation of remarkable metallacycle intermediates. The synthetic utility of the method is demonstrated by the synthesis of pharmacologically relevant triazolyl diaryl amines via a Cu(i ) catalyzed relay cycloaddition and Ullmann coupling sequence.